UJI STABILITAS FISIK DAN AKTIVITAS SEDIAAN LOTION ANTIOKSIDAN EKSTRAK DAUN KELOR (MORINGA OLEIFERA L.) DENGAN METODE DPPH - More, Evanisia; Kristyanti, Yulia; Beama, Christin A; Seran, Yuliana Caranina (Jurnal Farmasi & Sains Indonesia, 2025)
The Moringa plant (Moringa Oleifera Lamk) is one of the plants that is used for nutritional and health needs. Moringa leaves contain tannin compounds, steroids and triterpenoids, flavonoids, saponins, alkaloids, which have antioxidant activity. The aim of this research is to determine the physical stability of the Moringa leaf extract lotion preparation and to determine the antioxidant activity of the Moringa leaf extract lotion preparation using the DPPH method. This type of research is an experimental study consisting of 4 test groups, namely lotion preparation without extract, 1% Moringa leaf extract lotion preparation, 3% Moringa leaf extract lotion preparation and 5% Moringa leaf extract lotion preparation. The parameter observed was the storage of the Moringa leaf extract lotion preparation for 1 month. The lotion preparation of Moringa Oleifera L. leaf extract at concentrations of 0%, 1%, 3% and 5% showed no significant changes in the organoleptic test, homogeneity test, pH test, viscosity test, spreadability test and stickiness test so it is said that the preparation is stable during storage. Moringa leaf extract (Moringa Oleifera L.) lotion preparations with concentrations of 0%, 1%, 3% and 5% have IC50 values ​​respectively, namely (86.35), (66.60), (44.12), (11.89). Keywords: Moringa plant (Moringa Oleifera L.), lotion preparation, antioxidant